On- versus off-bike power training in professional cyclists: A randomized controlled trial - Valenzuela, P. L.; Gil-Cabrera, J.; Talavera, E.; Alejo, L. B.; Montalvo-Pérez, A.; Rincón-Castanedo, C.; Rodríguez-Hernández, I.; Lucia, A.; Barranco-Gil, D. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To compare the effectiveness of resistance power training (RPT, training with the individualized load and repetitions that maximize power output) and cycling power training (CPT, short sprint training) in professional cyclists.